Development of voice control and home security for smart home automation - Abidi, M.Ebrahim; Asnawi, Ani Liza; Mohamed Azmin, Nor Fadhillah; Jusoh, Ahmad Zamani; Ibrahim, Siti Noorjannah; Mohd Ramli, Huda Adibah; Abdul Malek, Norun (IEEE, 2018)
This paper presents a remote development of voice control and home security for smart home automation system using Arduino mega, GSM SIM900A, Bluetooth module, and HC-SR04 ultrasonic sensor. A microcontroller is programmed to control up to four home appliances via Bluetooth technology and transmit the received signal from sensor to user smartphone. Nowadays, there have been many commercials and research projects on smart homes but most of these products utilize remote control which have button on touch screen. In addition, there is also a need to give supporting system for people especially to the elderly, disabled, and increase their home security. Hence, we proposed a development of a wireless remote control for home gadgets which can be controlled with voice. This proposed system is expected to recognize human voice using voice reader android application to turn on and off home appliance. Another important feature developed in this project is on the detection of movement, using ultrasonic sensor, in which the signal is converted to message and forwarded to the mobile user via GSM module. The accuracy of the system is found to be above 95% and the electrical loads have been successfully controlled using voice command in controlling their home. In order for the system to work, it is necessary to power up Arduino Mega by 12V DC adaptor and connecting all AC power loads to the electricity. In this project, the proposed prototype of smart home automation system is implemented and tested on hardware so the user can control certain number of home appliances using voice.